A Study on the Mushrooms Demand through the Mushroom Agropreneurs’ Perspective in Selangor - Rosmiza M.Z.; Rosniza Aznie Che Rose; Mazdi Marzuki; Jabil Mapjabil (Penerbit Universiti Pendidikan Sultan Idris, 2018)
The global per capita consumption of mushrooms has been increasing. The rise in market demand for mushrooms was triggered by the potential of mushrooms in the pharmaceutical, nutraceutical, cosmeceutical, and related industries. This study focuses on evaluating the factors that contribute to the demand for mushrooms in Selangor. The study also views the demand levels based on the major ethnic groups in Selangor. Additionally, the study assesses demand from the perspective of agropreneurs who cultivate mushrooms in Selangor. The sample pool consists of 36 agropreneurs. Selangor was chosen as the research area because the demand and supply of mushrooms are the highest in Malaysia.Results highlighting that health factors involving high medical potential and nutritional value are the main drive for the high demand of mushrooms in Selangor as well as the taste factor. The promotions, peer ecommendation, and reasonable pricing are also affecting the demand level in the market. Ever-increasing demand presents agropreneurs with an opportunity to increase their production levels as well as to improve their marketing strategies. An increase in demand and the ability to meet the demand effectively will boost the diverse potential of mushroom products, which will in turn strengthen the agro food industry in Malaysia.